Using the protection motivation theory to examine the effects of fear arousal on the practice of social distancing during the COVID-19 outbreak in rural areas - Adunlin, Georges; Adedoyin, A. Christson A.; Adedoyin, Oreoluwa O.; Njoku, Anuli; Bolade-Ogunfodun, Yemisi; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2021)
The commentary elucidates the importance of Protection Motivation Theory (PMT) as a theoretical framework to encourage the practice of social distancing in rural areas as the world grappled with the pandemic of COVID-19 outbreak.
_eprint: https://doi.org/10.1080/10911359.2020.1783419
Keywords: COVID-19; Protection motivation theory; dept.pch; peer-reviewed; rural areas; social distancing

Cancers in Rural Areas in the United States - Njoku, A.; Wakeel, F. (Foundations of Rural Public Health in America, 2021)
Foundations of Rural Public Health in America spans a wide variety of important issues affecting rural public health, including consumer and family health, environmental and occupational health, mental health, substance abuse, disease prevention and control, rural health care delivery systems, and health disparities. Divided into five sections, the book covers understanding rural communities, public health systems and policies for rural communities, health disparities in rural communities and among special populations, and advancing rural health including assessment, planning and intervention. Written by a multidisciplinary team of experienced scholars and practitioners, this authoritative text comprehensively covers rural health issues today.
Google-Books-ID: AN0PEAAAQBAJ
Keywords: Medical / Public Health; dept.pch

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities - Balasuriya, Lilanthi; Santilli, Alycia; Morone, Jennifer; Ainooson, Jessica; Roy, Brita; Njoku, Anuli; Mendiola-Iparraguirre, Andrea; O’Connor Duffany, Kathleen; Macklin, Bernard; Higginbottom, Jackson; Fernández-Ayala, Celina; Vicente, Genesis; et al. (JAMA Network Open, 2021)
Black and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic.To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities.This community-partnered qualitative study conducted semistructured, in-depth focus groups with Black and Latinx participants from March 17 to March 29, 2021, using a secure video conferencing platform. Participants were recruited through emails from local community-based organizations, federally qualified health centers, social service agencies, the New Haven, Connecticut, Health Department, and in-person distribution of study information from community health workers. A total of 8 focus groups were conducted, including 4 in Spanish and 4 in English, with 72 participants from a diverse range of community roles, including teachers, custodial service workers, and health care employees, in New Haven, Connecticut. Data were analyzed from March 17 to July 30, 2021.Interviews were audio-recorded, transcribed, translated, and analyzed using an inductive content analysis approach. Themes and subthemes were identified on the acceptability and accessibility of the COVID-19 vaccine among participants who identified as Black and/or Latinx.Among 72 participants, 36 (50%) identified as Black, 28 (39%) as Latinx, and 8 (11%) as Black and Latinx and 56 (78%) identified as women and 16 (22%) identified as men. Participants described 3 major themes that may represent facilitators and barriers to COVID-19 vaccinations: pervasive mistreatment of Black and Latinx communities and associated distrust; informing trust via trusted messengers and messages, choice, social support, and diversity; and addressing structural barriers to vaccination access.The findings of this qualitative study may impact what health care systems, public health officials, policy makers, health care practitioners, and community leaders can do to facilitate equitable uptake of the COVID-19 vaccine. Community-informed insights are imperative to facilitating COVID-19 vaccine access and acceptance among communities hardest hit by the pandemic. Preventing the further widening of inequities and addressing structural barriers to vaccination access are vital to protecting all communities, especially Black and Latinx individuals who have experienced disproportionate death and loss from COVID-19.
73 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Adult; African American; African Americans; Article; Black person; COVID-19 Vaccines; Connecticut; Female; Focus Groups; Health Services Accessibility; Hispanic; Hispanic Americans; Humans; Male; Middle Aged; Patient Acceptance of Health Care; SARS-CoV-2 vaccine; South and Central America; Trust; Young Adult; adolescent; adult; aged; community; content analysis; controlled study; coronavirus disease 2019; dept.pch; e-mail; employment; female; health auxiliary; health behavior; health care access; health care delivery; health care personnel; health care system; health center; health disparity; human; information processing; male; medical information; middle aged; outcome assessment; pandemic; patient attitude; peer-reviewed; public health service; qualitative research; risk factor; semi structured interview; social support; social worker; teacher; trust; vaccination; videoconferencing; young adult

Changing the narrative: Structural barriers and racial and ethnic inequities in COVID-19 vaccination. - Njoku, Anuli; Joseph, Marcelin; Felix, Rochelle (International journal of environmental research and public health, 2021)
The COVID-19 pandemic has disproportionately affected racial and ethnic minority groups in the United States. Although a promising solution of the COVID-19 vaccination offers hope, disparities in access again threaten the health of these communities. Various explanations have arisen for the cause of disparate vaccination rates among racial and ethnic minorities, including discussion of vaccine hesitancy. Conversely, the role of vaccine accessibility rooted in structural racism as a driver in these disparities should be further explored. This paper discusses the impact of structural barriers on racial and ethnic disparities in COVID-19 vaccine uptake. We also recommend public health, health system, and community-engaged approaches to reduce racial disparities in COVID-19 disease and mortality. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
80 citations (Crossref) [2023-10-31] https://www.mdpi.com/1660-4601/18/18/9904/pdf ; http://europepmc.org/article/MED/34574827 ; https://pubmed.ncbi.nlm.nih.gov/34574827/ ; https://www.ncbi.nlm.nih.gov/pmc/articles/PMC8470519
Keywords: African American; Article; Black person; COVID-19; COVID-19 Vaccines; Coronavirus; Ethnic Groups; Health Status Disparities; Healthcare Disparities; Humans; Latino people; Minority Groups; Pandemics; SARS-CoV-2; SARS-CoV-2 vaccine; United States; Vaccination; access to computer; access to information; black population; communication barrier; coronavirus disease 2019; dept.pch; ethnic disparity; ethnic group; ethnic minority; health care access; health care disparity; health care system; health disparity; health literacy; health services; human; immigrant; infection prevention; internet access; language ability; mass immunization; minority group; mortality; outcome assessment; pandemic; peer-reviewed; public access; public health service; race difference; racial disparity; racism; social behavior; social determinants of health; social inequality; structural barrier; traffic and transport; vaccination

COVID-19 and environmental racism: Challenges and recommendations - Njoku, Anuli (European Journal of Environment and Public Health, 2021)
25 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Exposure to Di-2-ethylhexyl phthalate (DEHP) and infertility in women, NHANES 2013-2016. - Trnka, Brittany; Polan, Maya; Zigmont, Victoria A. (Reproductive toxicology (Elmsford, N.Y.), 2021)
Di-2-ethylhexyl phthalate (DEHP) exposure is widespread in the general population and previous research has suggested that it contains endocrine-disrupting properties that can adversely affect the reproductive health system. The objective of this study was to use the 2013–2016 National Health and Nutrition Examination Survey (NHANES) data to assess the potential association between DEHP exposure and infertility in women. Using a nationally representative, cross-sectional study design, we used multiple logistic regression to measure the association of urinary metabolites of DEHP with self-reported history of infertility among women. Four metabolites of DEHP were examined: mono(2-ethylhexyl)phthalate (MEHP), mono(2-ethyl-5-hydroxy-hexyl)phthalate (MEHHP), mono(2-ethyl-5-oxy-hexyl) phthalate (MEOHP), and mono(2-ethyl-5-carboxy-pentyl)phthalate (MECPP). These metabolites were calculated into a molar sum of DEHP (∑DEHP) and split into quartiles for analysis. After adjusting for age and race, ∑DEHP was associated with increased odds of infertility for the second quartile (AOR = 2.35, 95% CI [1.24,4.44], p = 0.01) and third quartile (AOR = 2.83, 95% CI [1.57, 5.10], p ¡ 0.01) when compared to the first quartile (reference). The adjusted OR for the highest quartile of ∑DEHP found no association and it was not statistically significant (AOR = 0.99, 95 %CI [0.57, 1.73], p = 0.98). The findings of this study add to the already complex existing literature on phthalate exposure and infertility. These findings warrant further population-based cohort studies on phthalate exposure and their relationship to infertility in humans. © 2021 Elsevier Inc.
18 citations (Crossref) [2023-10-31]
Keywords: Adult; Article; Cross-Sectional Studies; Diethylhexyl Phthalate; Endocrine Disruptors; Environmental Exposure; Environmental Pollutants; Female; Humans; Infertility; Male; Middle Aged; Nutrition Surveys; Phthalic Acids; Young Adult; adult; cohort analysis; controlled study; cross-sectional study; dept.pch; drug urine level; electrospray mass spectrometry; endocrine disruptor; environmental exposure; exposure; female; female infertility; high performance liquid chromatography; human; infertility; limit of detection; major clinical study; male; middle aged; mono(2 ethyl 5 carboxy pentyl)phthalate; mono(2 ethyl 5 hydroxy hexyl)phthalate; mono(2 ethyl 5 oxy hexyl)phthalate; mono-(2-ethylhexyl)phthalate; nutrition; peer-reviewed; phthalic acid; phthalic acid 2 ethylhexyl monoester; phthalic acid bis(2 ethylhexyl) ester; phthalic acid derivative; pollutant; questionnaire; sensitivity analysis; toxicity; unclassified drug; young adult

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34670106/
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Book Review: Disaster by choice. How our actions turn natural hazards into catastrophes Ilan Kelman Oxford, UK: Oxford University Press, 2020. ISBN: 9780198841340. - Jung, Betty C. (World Medical & Health Policy, 2021)
1 citations (Crossref) [2023-10-31]
Keywords: book.review; dept.pch

Book Review: FrielSharon. Climate Change and the People's Health. New York, NY: Oxford University Press, 2019. $29.95. pp. 232. ISBN: 9780190492731. - Jung, Betty C. (World Medical & Health Policy, 2021)
0 citations (Crossref) [2023-10-31] Place: United States
Keywords: Health Policy; book.review; dept.pch

Comprehensive Contraceptive Education Inter-vention in a College Setting: Design and Methodology - Evans, M.; De Leon, B.; Bathrick, R.; Ricupero, A. (Journal of Public Health Issues and Practices, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed

Collaborating With Parks and Recreation Departments to Address Youth Health - Risisky, Deb; MacGregor, James (Health Promotion Practice, 2021)
Adolescence is an important time for addressing health, including mental health, obesity, substance use, and food insecurity. As the myriad health and wellness needs of community members expands, it becomes increasingly difficult for one profession alone to address these needs. The park and recreation field was founded to address the health and wellness needs of people, and much of their programming is focused on youth. Thus, municipal park and recreation departments are becoming increasingly involved in collaborative partnerships with other health-serving agencies within their community. This study explored park and recreation directors’ experiences in collaborating with health agencies to better address health and wellness factors that affect the youth in their communities. This phenomenological qualitative study employed in-depth interviews with park and recreation directors and used thematic analysis. Nine interviews were conducted from four of the six New England states. The most common health concern seen by the directors was mental health, primarily behavioral health challenges. Parks and recreation collaboration with public health organizations ranged from none to close collaborations; directors regularly spoke about wanting to strengthen their collaborations. Public health and park and recreation staff have similar challenges with staffing and resources; additionally, they have complimentary skills with regard to planning and implementing health-related programs. For that reason, creating purposeful collaborative partnerships between public health agencies and park and recreation departments, focused on measurable outcomes, may increase benefits to the health of youth in a community.
0 citations (Crossref) [2023-10-31]
Keywords: adolescent health; collaboration; dept.pch; dept.rec; mental health; multisector; park and recreation; peer-reviewed; physical activity; prevention; trauma

Barriers and Motivators to Opioid Treatment Among Suburban Women Who Are Pregnant and Mothers in Caregiver Roles. - Boeri, Miriam; Lamonica, Aukje K; Turner, Jeffrey M; Parker, Amanda; Murphy, Grace; Boccone, Carly (Frontiers in psychology, 2021)
Women of childbearing age who misuse opioids are a particularly vulnerable population, and their barriers to treatment are unique because of their caregiver roles. Research on treatment for opioid use generally draws from urban and rural areas. This study fills a gap in research that focuses on barriers and motivators to opioid treatment in suburban areas. The aim of this study was to give voice to suburban pregnant women and mothers caring for children while using opioids. Ethnographic methods were used for recruitment, and 58 in-depth interviews were analyzed using a modified grounded theory approach. Barriers to medication-assisted treatment (MAT) included stigma, staff attitudes, and perceptions the women had about MAT treatment. Barriers associated with all types of treatment included structural factors and access difficulties. Relationships with partners, friends, family, and providers could be barriers as well as motivators, depending on the social context of the women's situation. Our findings suggest increasing treatment-seeking motivators for mothers and pregnant women by identifying lack of resources, more empathetic consideration of social environments, and implementing structural changes to overcome barriers. Findings provide a contemporary understanding of how suburban landscapes affect mothers' treatment-seeking for opioid dependence and suggest the need for more focus on emotional and structural resources rather than strict surveillance of women with opioid dependence who are pregnant or caring for children. Copyright © 2021 Boeri, Lamonica, Turner, Parker, Murphy and Boccone.
2 citations (Crossref) [2023-10-31] Place: Switzerland Boeri, Miriam. Department of Sociology, Bentley University, Waltham, MA, United States. Lamonica, Aukje K. Department of Public Health, Southern Connecticut State University, New Haven, CT, United States. Turner, Jeffrey M. Department of Public Health, Southern Connecticut State University, New Haven, CT, United States. Parker, Amanda. Department of Sociology, Bentley University, Waltham, MA, United States. Murphy, Grace. Department of Sociology, Bentley University, Waltham, MA, United States. Boccone, Carly. Department of Sociology, Bentley University, Waltham, MA, United States.
Keywords: dept.pch; peer-reviewed

Correlates of Strength and Balance Training Exercises in Older African American Adults. - Jiakponnah, Nwanyieze; Ngozi MD, MPH; Unson, Christine; Chukwurah, Queendaleen; Chinenye MD, MPH (Gerontologist, 2021)
Background and Objectives: This study investigated the behavioral and psychological correlates of strength and balance training (SBT) participation among older African Americans. Research Design and Methods: A cross-sectional survey of 90 older African Americans (M = 66.7 ± 8.7 years; 70% female) was conducted to assess correlates of intention to undertake SBT exercises and the number of days that they currently engage in SBT. The Theory of Planned Behavior (TPB) and the threat appraisal of the Protection Motivation Theory (PMT) were used as frameworks for the analyses. Results: The intention to do SBT exercises was positively associated with favorable attitudes and subjective norm, knowledge about the benefits of SBT, and hours worked per week. The frequency of SBT participation was significantly correlated with behavioral intention, high fear of falling, and a low score on the kinesiophobia scale. Discussion and Implications: This study demonstrated the utility of the TPB and PMT's threat appraisal construct in modeling intention and number of days of SBT participation among African American older adults. The study affirmed the link between intention and behavior and between knowledge of the benefits of SBT and intention. Fear of falling's positive association with days of SBT suggests that respondents' saw SBT's efficacy in reducing falls. The unique contributions of this study are the inclusions of kinesiophobia as a correlate and multiple threat appraisals in the PMT. Health promotion interventions should consider the interrelationship among these constructs. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.
0 citations (Crossref) [2023-10-31] Place: (C) Copyright Oxford University Press 2021.
Keywords: Accidental Falls; African American; African Americans; Aged; Attitude; Cross-Sectional Studies; Exercise; Fear; Fear of falling; Female; Humans; Intention; Kinesiophobia; Male; Psychological Theory; Subjective norm; Surveys and Questionnaires; Theory of Planned Behavior; adult; aged; article; behavior; controlled study; cross-sectional study; dept.pch; exercise; falling; fear; fear of falling; female; health promotion; human; male; motivation; peer-reviewed; prevention and control; psychological theory; questionnaire; theoretical study

The Socialization of Unpaid Family Caregivers: A Scoping Review. - McAllum, Kirstie; Simpson, Mary; Unson, Christine; Fox, Stephanie; Kilpatrick, Kelley (Res Aging, 2021)
As unpaid family caregiving of older adults becomes increasingly prevalent, it is imperative to understand how family caregivers are socialized and how they understand the caregiving role. This PRISMA-ScR-based scoping review examines the published literature between 1995-2019 on the socialization of potential and current unpaid family caregivers of older adults. Of 4,599 publications identified, 47 were included. Three perspectives of socialization were identified: (1) role acculturation; (2) role negotiation and identification; and (3) specialized role learning. The findings show how socialization involves different contexts (e.g., cultures), imperatives for action (e.g., circumstances), socialization agents (e.g., family), processes (e.g., modeling), and internal (e.g., normalization) and external (e.g., identification) consequences for caregivers. Future research could fruitfully explore how caregivers manage key turning points within the socialization process, disengage from the caregiving role, and negotiate the socialization and individualization processes within diverse cultural and funding contexts., (C)2021Sage Publications
2 citations (Crossref) [2023-10-31] Place: (C)2021Sage Publications
Keywords: Aged; Caregivers; Family; Humans; Socialization; aged; care behavior; caregiver; caregiving; cultural factor; dept.pch; elder care; family; funding; human; individualization; intergenerational support; learning; negotiation; peer-reviewed; review; socialization

Helps my family survive hard times: An innovative summertime food relief program in new haven, connecticut - Zigmont, V.A.; Tomczak, S.M.; Bromage, B.; Vignola, A.; Gallup, P (Journal of Poverty, 2021)
To achieve healthy communities, addressing food insecurity (FI) is critical. This study describes a unique food distribution program combining a mobile Summer Food Service Program (SFSP) for children with a mobile pantry for adults. A survey (n = 153) of participants at six locations in New Haven Connecticut revealed that 36% reported FI and 76% were first-time pantry users. Three- quarters participated in SNAP, WIC, or both, and two-thirds had children who were fed by SFSP. Major federal programs do not eliminate FI, therefore local voluntary organizations are essential partners to address the food crisis caused by the COVID-19 pandemic.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102796303
Keywords: dept.pch; dept.swk; peer-reviewed

Application of the Weathering Framework: Intersection of Racism, Stigma, and COVID-19 as a Stressful Life Event among African Americans - Wakeel, Fathima; Njoku, Anuli (Healthcare, 2021)
The disproportionate impact of coronavirus disease 2019 (COVID-19) on African American communities necessitates an increased focus on the intersectional roles of racism, stigma, and other social determinants of health in influencing disease and mortality risk. The Weathering Framework is applied to demonstrate the dynamic interrelationships between these factors and to conceptualize COVID-19 as a stressful life event that will have profound health implications over the life course for African Americans. Recommendations for population health research, interventions and policies aimed at reducing COVID-19 incidence and mortality, and mitigation of the long-term impacts of the pandemic on communities of color are discussed.
22 citations (Crossref) [2023-10-31] Number: 2
Keywords: Blacks/African Americans; COVID-19/coronavirus; dept.pch; health disparities; peer-reviewed; race/ethnicity; racism; social determinants of health; stigma; systemic racism

Photovoice for Social Justice: Visual Representation in Action - Breny, Jean M. (Sage, 2021)
"Photovoice for Social Justice, the latest volume in Sage's Qualitative Research Methods Series, helps readers in the health and social sciences learn the foundations and applications of this exciting qualitative method. Authors Jean M. Breny and Shannon L. McMorrow approach photovoice as not only a community-based participatory research method, but as a method for social justice, centering community participants, organizations, and policy makers at the heart of this research method. Special topics relating to social justice include a focus on ethics and working with marginalized communities, sensitive concerns during data collection, and presenting the work to communities and policymakers, as well as academics. Written for students and researchers new to photovoice, this brief text takes readers from the process of conceptualizing and implementing a photovoice study to analyzing data and finally presenting the results of the study. The book concludes with suggestions for future iterations of photovoice, including web based resources and digital storytelling. The authors take into account the realities of photovoice as a method by providing practical, applied tools including sample consent forms, presentations, recruitment flyers, and photo-taking tips. Using Photovoice for Social Justice, new and experienced researchers can design, implement, and analyze their photovoice projects" –
Keywords: Methodology; Medicine; Methodology; Photography in the social sciences; Participant observation; Action research; Research; Social aspects; Social service; dept.pch; faculty_collection

Circumstances of overdose among suburban women who use opioids: Extending an urban analysis informed by drug, set, and setting. - Lamonica, Aukje K; Boeri, Miriam; Turner, Jeffrey (The International journal on drug policy, 2021)
BACKGROUND: Opioid overdoses are primarily discussed by the pharmacological properties of the drugs used. Research shows that other factors such as the social/physical environment and the mental/emotional states can have an impact on overdose events. Ataiants and colleagues (2020) used Zinberg's "drug, set, and setting" framework to identify circumstances surrounding overdose experiences of street-involved women in Philadelphia. The aim of this paper is to extend their analysis to a diverse sample of suburban women who experienced overdoses., METHODS: The mixed-methods design consisted of ethnographic fieldwork, in-depth interviews, and brief surveys with 32 suburban women who use opioids. Inductive theoretical reasoning and constant comparative analysis facilitated themes emerging within the "drug, set, and setting" framework., RESULTS: Eighteen out of 32 women identified "drug" as the primary factor involved in their overdose events. Major themes were an inability to identify the synthetic opioid fentanyl, lack of knowledge or control over how much to use, poly-substance use, and an insufficient understanding of risks. Eleven out of 32 women linked "set" to their overdose experiences. Themes included emotional trauma, such as death of a child, child custody issues, and mental health conditions, such as depression. Six out of 32 women associated "setting" with one of their overdose experiences. Themes were related to being with friends or partners that used, and having recently been released from treatment or incarceration., CONCLUSION: Findings show similar themes found among an urban sample, adding insight on the need for effective overdose interventions targeted for suburban populations. The opioid crisis is not confined to the cities, and neither should services aimed at addressing opioid overdose. The knowledge provided here can help policy makers support female-centered harm reduction services not only in urban areas but also in the suburbs. Copyright © 2020. Published by Elsevier B.V.
9 citations (Crossref) [2023-10-31] Place: Netherlands Lamonica, Aukje K. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States. Electronic address: lamonicaa1@southernct.edu. Boeri, Miriam. Bentley University, 175 Forest Street, Waltham, MA 02452, United States. Turner, Jeffrey. Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, United States.
Keywords: *Drug Overdose; *Pharmaceutical Preparations; Analgesics; Analgesics; Opioid/tu [Therapeutic Use]; Article; Child; Drug Overdose; Drug Overdose/dt [Drug Therapy]; Drug Overdose/ep [Epidemiology]; Female; Fentanyl; Humans; Opioid; Pennsylvania; Pharmaceutical Preparations; Philadelphia; adult; child; child custody; childhood mortality; controlled study; depression; dept.pch; drug; drug overdose; ethnography; female; fentanyl; human; incarceration; inductive reasoning; interview; major clinical study; mental health; narcotic analgesic agent; opiate addiction; peer-reviewed; polypharmacy; priority journal; psychotrauma; risk factor; suburban area; urban area; women's health